Achtsamkeitstraining als psychotherapeutische Interventionsmethode: Konzeptklärung, klinische Anwendung und aktuelle empirische Befundlage - Berking, Matthias; von Känel, Miriam (Psychotherapie Psychosomatik Medizinische Psychologie, 2007)
With mindfulness-based interventions becoming increasingly popular this review outlines: 1. How mindfulness is defined and conceptualized, 2. How mindfulness is applied in psychotherapy, 3. How effective mindfulness-based interventions are and 4. How the effectiveness of these methods might be explained. Findings show that mindfulness can be seen as a multidimensional concept which is the core or an important component of several psychotherapeutical methods that have been shown to be effective in the treatment of different psychological problems and disorders. With regard to possible mechanisms of change it is argued that enhancing patients' skills to accept and tolerate aversive experiences can be seen as a specific and important effect of these approaches. Future research should try to clarify for whom these skills are particularly important, and how these skills can be taught to patients who are less open for mindfulness-based approaches. © Georg Thieme Verlag KG Stuttgart.
Created from Fastlane, Scopus look-up
Keywords: Effectiveness; Mindfulness; Psychotherapy; Review; Treatment-outcome